ROLLING AMONG CALABI-YAU VACUA - Candelas, P; Green, P; Hubsch, T (1990)
For a very large number of Calabi-Yau manifolds of many different numerical invariants and hence distinct homotopy types, the relevant moduli spaces can be assembled into a connected web. Here we study the geometry of these moduli spaces, especially near the interfacing regions which correspond to conifolds, certain rather mild singularizations of the manifolds in question. In the natural metric, which we show to coincide also with the point field limit of the Zamolodchikov metric, all the distances in this web are finite.